Collision behaviour of a smaller particle into a larger stationary droplet - Mitra, S.; Doroodchi, E.; Pareek, Vishnu; Joshi, J.; Evans, G. (ELSEVIER SCIENCE BV, 2015)
The present study investigates the collision behaviour of a smaller particle into a larger stationary droplet – a phenomenon related to many process engineering applications. Experimentally, the collision process was studied using high speed video imaging involving glass ballotini particles (diameter: 1.13 ± 0.02 mm) and a supported stationary water droplet (diameter 3.41 ± 0.01 mm) at different particle impact velocities (Weber number range: 0.2–13.5). A transition from partial to complete penetration was observed with decrease in sinking time and significant shape deformation of the droplet when Weber number was increased. Numerically, a one dimensional transient force balance approach was adopted which included contributions of six major forces during the penetration process, including: gravity, capillary, fluid drag, buoyancy, pressure and added mass. It was found that the capillary force controlled the interaction process. Recognizing the limitation of using the one dimensional model to capture the details of the collision physics especially the movement of three phase contact line (TPCL) on the particle surface, a 3D computational fluid dynamics (CFD) model was developed using the multiphase volume of fluid (VOF) method combined with the dynamic meshing technique. The CFD model was in good agreement with experimental measurements of the sinking time of the particle and overall collision dynamics including shape deformation of the droplet.